Transitioning to civilian life: The importance of social group engagement and identity among Australian Defence Force veterans. (August 2022) - Barnett, Anthony; Savic, Michael; Forbes, David; Best, David; Sandral, Emma; Bathish, Ramez; Cheetham, Alison; Lubman, Dan I
Objective: Veterans transitioning to civilian life after leaving the military face unique health concerns. Although there is a significant body of research exploring veterans' experiences of transition and predictors of well-being, there are limited studies examining how social group engagement influences veterans' transition. We explored how Australian Defence Force veterans' social group engagement and identity influenced their adjustment to civilian life and well-being. Methods: Forty Australian veterans (85% male; mean age = 37 years, range = 25–57 years) took part in in-depth, semi-structured interviews. Participants completed two mapping tasks (a social network map and life course map) that provided a visual component to the interviews. Interview transcripts were analysed thematically and interpreted by adopting a social identity approach. Results: Joining the military involved a process of socialisation into military culture that for most participants led to the development of a military identity. An abrupt or difficult discharge from defence was often associated with a negative impact on social group engagement and well-being in civilian life. Veterans' social group memberships may act not only as positive psychological resources during transition but also as a potential source of conflict, especially when trying to re-engage with civilian groups with different norms or beliefs. Military values inscribed within a veteran's sense of self, including a strong sense of service, altruism and giving back to their community, may operate as positive resources and promote social group engagement. Conclusion: Engaging with supportive social groups can support transition to civilian life. Reintegration may be improved via effective linkage with programmes (e.g. volunteering, ex-service support organisations) that offer supportive social networks and draw upon veterans' desire to give back to community. Social mapping tasks that visualise veterans' social group structures may be useful for clinicians to explore the roles and conflicts associated with veterans' social group memberships during transition.